Sosialisasi Hukum Tentang Hak-Hak Keperdataan Masyarakat Yang Timbul Dari Perkawinan Dan Perjanjian - Pietersz, Jemmy Jefry; Latupono, Barzah; Kuahaty, Sarah Selfina (AIWADTHU: Jurnal Pengabdian Hukum, 2024)
Introduction: Society as a legal subject has civil rights in legal interactions within the community. These civil rights come in many forms, and the socialization carried out includes marriage rights and contract rights. Therefore, legal socialization is necessary to provide enlightenment regarding civil rights.Purposes of Devotion: The purpose of this community service is to transform information and legal knowledge related to civil rights of the community.Method of Devotion: The outreach activities are carried out by conveying a) information and legal knowledge; b) dissemination of marriage law; and c) dissemination of contract law.Results of the Devotion: Increased public understanding of rights arising from civil law relationships, particularly marriage and contract. The community obtains information from the aspect of marriage law regarding the requirements of marriage, rights and obligations within marriage, and the legal consequences of marriage. From the aspect of contract law regarding the validity of unwritten contracts that are often made by the community and their legal consequences. This legal education is expected to provide guidance on legal protection and preventive measures.